Shrek 2 [videorecording] - Adamson, Andrew; Asbury, Kelly; Vernon, Conrad; DreamWorks Home Entertainment (Firm); Universal Studios Home Video (Firm) (Universal City, CA : DreamWorks Home Entertainment, 2009)
Right after Shrek and Princess Fiona's honeymoon, the newly wed couple goes to Princess Fiona's parents for dinner. When a Fairy Godmother discovers Fiona and Shrek are married she reminds the king about a deal they areed on years ago, that Fiona should have married her son, who happens to be Prince Charming. The King then hires a cat named Puss-in-Boots, a sword fighting cat and ogre slayer, to kill Shrek.